Preferensi Bahan Bakar Minyak Bersubsidi dan Nonsubsidi di Kalangan Pegawai Pemerintah Kota Bandar Lampung - Simanjuntak, Wira Kartua Halomoan; Putra, Sasana; Putri Ofrial, Siti Anugrah Mulya; Sulistyorini, Dr. Rahayu (Universitas Lampung, 2022)
Transportation is defined as the activity of moving passengers and goods from one place to another, in which there is an element of movement. Transportation plays an important role in the development and development of infrastructure in urban areas. This is the main reason for choosing those that are considered efficient in terms of fuel in meeting the transportation needs of the vehicles used. According to the author's observations, people tend to prefer to buy subsidized fuel because of the higher prices. cheap, so willing to wait in long lines and cause the road to be consumed by queues that disturb other road users. Fuel oil itself is divided into 2 groups, namely subsidized and non-subsidized. The problem of adjusting subsidized fuel prices has also developed a discourse regarding who is entitled to subsidized fuel based on Presidential Regulation Number 43 of 2014 as amended by Presidential Regulation Number 43 of 2018 concerning the supply, distribution, and retail selling price of BBM. Data collection was carried out directly in the field by giving questionnaires and asking directly to Bandar Lampung City Government Employees. After that, perform an analytical test by evaluating the tariff according to the ability to buy Ability To Pay (ATP) and the willingness of consumers to buy Willingness To Pay (WTP) using the Analytical Hierarchy Process (AHP) method. From this, the authors are interested in conducting research with the title: